Effect of the formulation on mucoadhesive spray-dried microparticles containing iron for food fortification. (January 2023) - Baldelli, Alberto; Liang, Diana Yumeng; Guo, Yigong; Pratap-Singh, Anubhav
Abstract: Food fortification through iron encapsulated spray-dried microparticles can alleviate the iron deficiency. Here, we analyze the impact of the ratio between the wall and the bulk material, the amount of solids, the type of wall material, and the type of iron compound on the properties of spray dried powder. Optimal formulations contain equal weight percentages of iron compound, bulk material, and wall material. In this case, spray-dried microparticles show an average projected area equivalent diameter of 4.3 μm with a bioavailability of 60%. Moreover, the encapsulation of iron gluconate reduces the toxicity of Caco-2 and Hep-G2 at any quantities of iron below 12 mg/ml. We verified that most mucoadhesive microparticles include dextran or hydroxyl-methylcellulose; the detachment force between microparticles with a shell made of hydroxyl-methylcellulose and the human intestine is 1.6 N. Moreover, the encapsulation of iron gluconate via spray drying increases Caco-2 iron absorption by 38% compared to non-encapsulated material. An opposite response was observed using iron fumarate, where the absorption was reduced by 31% when the iron compound was encapsulated. Graphical abstract: Image 1 Highlights: Encapsulation is effective with 1:1:1 of HP-MC, maltodextrin, iron gluconate. HP-MC shows the highest muco-adhesivity with intestine and stomach walls. Encapsulation of iron gluconate doubles the cell viability with Caco-2. Dextran in the formulation produces 100% of the release rate after only 20 min.